Global estimates on the number of people blind or visually impaired by glaucoma: a meta-analysis from 2000 to 2020 - Bourne, Rupert; Jonas, Jost B. (Eye, 2024)
To estimate global and regional trends from 2000 to 2020 of the number of persons visually impaired by glaucoma and their proportion of the total number of vision-impaired individuals.
Vision Loss Expert Group of the Global Burden of Disease Study and the GBD 2019 Blindness and Vision Impairment Collaborators: Rupert R.A. Bourne, Jost B. Jonas, David Friedman, Vinay Nangia, Alain Bron, Ian Tapply, Arthur G. Fernandes, Maria Vittoria Cicinelli, Alessandro Arrigo, Nicolas Leveziel, Serge Resnikoff, Hugh R. Taylor, Tabassom Sedighi, Mukkharram M. Bikbov, Tasanee Braithwaite, Ching-Yu Cheng, Nathan Congdon, Monte A. Del Monte, Joshua R. Ehrlich, Tim Fricke, João M. Furtado, Gus Gazzard, Ronnie George, M. Elizabeth Hartnett, Rim Kahloun, John H. Kempen, Moncef Khairallah, Rohit C. Khanna, Judy E. Kim, Van Charles Lansingh, Janet Leasher, Kovin S. Naidoo, Michal Nowak, Konrad Pesudovs, Tunde Peto, Pradeep Ramulu, Fotis Topouzis, Mitiadis Tsilimbaris, Ya Xing Wang, Ningli Wang, Seth Flaxman, Rupert R. A. Bourne, Jost B. Jonas, Robert James Casson, David S. Friedman, Vinay Nangia, Alain M. Bron, Ian Tapply, Arthur G. Fernandes, Maria Vittoria Cicinelli, Nicolas Leveziel, Paul Svitil Briant, Theo Vos, Serge Resnikoff, Yohannes Habtegiorgis Abate, Melsew Dagne Abate, Zahra Abbasi Dolatabadi, Mozhan Abdollahi, Richard Gyan Aboagye, Eman Abu-Gharbieh, Salahdein Aburuz, Qorinah Estiningtyas Sakilah Adnani, Shahin Aghamiri, Bright Opoku Ahinkorah, Danish Ahmad, Hamid Ahmadieh, Hooman Ahmadzadeh, Ayman Ahmed, Ahmad Samir Alfaar, Cyrus Alinia, Louay Almidani, Hubert Amu, Sofia Androudi, Abhishek Anil, Jalal Arabloo, Damelash Areda, Tahira Ashraf, Sara Bagherieh, Ovidiu Constantin Baltatu, Mehmet Firat Baran, Amadou Barrow, Azadeh Bashiri, Nebiyou Simegnew Bayileyegn, Fatemeh Bazvand, Alemshet Yirga Berhie, Jasvinder Singh Bhatti, Mukharram Bikbov, Marina G. Birck, Veera R. Bitra, Marija M. Bozic, Tasanee Braithwaite, Katrin Burkart, Yasser Bustanji, Zahid A. Butt, Muthia Cenderadewi, Vijay Kumar Chattu, Kaleb Coberly, Omid Dadras, Xiaochen Dai, Ana Maria Dascalu, Anna Dastiridou, Vinoth Gnana Chellaiyan Devanbu, Meghnath Dhimal, Daniel Diaz, Thao Huynh Phuong Do, Thanh Chi Do, Arkadiusz Marian Dziedzic, Joshua R. Ehrlich, Michael Ekholuenetale, Muhammed Elhadi, Mohammad Hassan Emamian, Mehdi Emamverdi, Hossein Farrokhpour, Getahun Fetensa, Florian Fischer, Ali Forouhari, Kayode Raphael Fowobaje, João M. Furtado, Aravind P. Gandhi, Miglas W. W. Gebregergis, Bárbara Niegia Garcia Goulart, Mesay Dechasa Gudeta, Sapna Gupta, Vivek Kumar Gupta, Veer Bala Gupta, Golnaz Heidari, Sung Hwi Hong, Hong-Han Huynh, Segun Emmanuel Ibitoye, Irena M. Ilic, Mustapha Immurana, Sathish Kumar Jayapal, Nitin Joseph, Charity Ehimwenma Joshua, Rim Kahloun, Himal Kandel, Ibraheem M. Karaye, Hengameh Kasraei, Getu Mosisa Kebebew, John H. Kempen, Mahmoud Tawfik KhalafAlla, Sudarshan Khanal, Mahalaqua Nazli Khatib, Kewal Krishan, Chandrakant Lahariya, Janet L. Leasher, Stephen S. Lim, Roy Rillera Marzo, Andrea Maugeri, Yang Meng, Tomislav Mestrovic, Manish Mishra, Nouh Saad Mohamed, Hoda Mojiri-forushani, Ali H. Mokdad, Hamed Momeni-Moghaddam, Fateme Montazeri, Admir Mulita, Christopher J. L. Murray, Mahdi Nabi Foodani, Ganesh R. Naik, Zuhair S. Natto, Biswa Prakash Nayak, Mohammad Negaresh, Hadush Negash, Dang H. Nguyen, Bogdan Oancea, Andrew T. Olagunju, Matthew Idowu Olatubi, Wael M. S. Osman, Uchechukwu Levi Osuagwu, Jagadish Rao Padubidri, Songhomitra Panda-Jonas, Shahina Pardhan, Seoyeon Park, Jay Patel, Arokiasamy Perianayagam, Konrad Pesudovs, Hoang Tran Pham, Elton Junio Sady Prates, Ibrahim Qattea, Fakher Rahim, Mosiur Rahman, Deepthi Rapaka, Salman Rawaf, Nazila Rezaei, Priyanka Roy, Basema Saddik, Umar Saeed, Sher Zaman Safi, Sare Safi, Joseph W. Sakshaug, Mohamed A. Saleh, Vijaya Paul Samuel, Abdallah M. Samy, Aswini Saravanan, Allen Seylani, Masood Ali Shaikh, Muhammad Aaqib Shamim, Mohammed Shannawaz, Bereket Beyene Shashamo, Maryam Shayan, Aminu Shittu, Emmanuel Edwar Siddig, Jasvinder A. Singh, Yonatan Solomon, Raúl A. R. C. Sousa, Seyyed Mohammad Tabatabaei, Mohammad Tabish, Jansje Henny Vera Ticoalu, Temesgen Mohammed Toma, Aristidis Tsatsakis, Guesh Mebrahtom Tsegay, Rohollah Valizadeh, Maria Viskadourou, Gizachew Tadesse Wassie, Nuwan Darshana Wickramasinghe, Dong Keon Yon, Yuyi You, Seth Flaxman, and Jaimie D. Steinmetz
Gesehen am 04.02.2025